Saberes produzidos na ação de ensinar matemática na EJA: contribuições para o debate sobre a formação inicial de educadores matemáticos na UFPA - ALVES, Osvando dos Santos (2004)
Throughout their teaching experience, teachers reelaborate, adapt and transmit the vast knowledge received along their initial educational process by the reflection of their own experience. This wide range of knowledge started from the teaching process, here Mathematics, becomes the basis of their professional identity. Due to the peculiarities of the Math students in the YAE (Young and Adults Education), this knowledge becomes specific too. Such peculiarities demands a reeducation, which, in most cases happens through a reflection. This research (named: Knowledge generated after the Math teaching experience in the EJA: contributions for the discussion over the graduation of Math teachers in UFPA.) aims to highlight the knowledge produced by the teaching experience process from what was said by Math teachers and trainees from YAE in the relations teachers x students, teachers x graduating contents and teachers x teachers. This is a critical look of teachers and senior trainees? own educational background and field experience, promoting an understanding, indicating guidelines for a graduation which can observe these peculiarities. For data collecting the instrument used were the controlled interview with teachers and trainees. The field experience knowledge regarding the curriculum, the students of the YAE, peculiarities of their adult life and the contextualization of the Math contents among others were highlighted. The characteristic of the reflections expressed by the teachers and trainees when speaking during the interview show that this knowledge is unnoticedly present and also that it needs to be highlighted, to have special attention and brought to discussion.